The London 2012 Olympic Games Opening Ceremony: History answers back. Issue 1 (1st April 2013) - Biressi, Anita; Nunn, Heather
This article highlights the distinctive turn in public discourse towards historical resources, analogies and stories to help citizens make sense of the current era of austerity through a selective analysis of the media coverage of the London 2012 Olympic Games. It argues that in straitened times British citizens are being asked to make do, to accept the rolling back of state provision and to modify their expectations of a civil society on the basis of historical myths as well as current realities. Having noted this, the article asks where on television are the counter-discourses that may also wish to lay a claim to a national history and to tell national stories and even to contest the dismantling of the welfare state? How might these spaces work to resist the prevalent criticism of public services, organized labour and popular protest and to defend the class (and other) politics and values with which these have been historically associated? In answer to these questions this article offers a brief consideration of the ways in which the 2012 London Olympics Opening Ceremony deployed history and historical reference.